Type-2 Diabetes and the Clinical Importance of Exaggerated Exercise Blood Pressure. Issue 10 (8th August 2022) - Schultz, Martin G.; Otahal, Petr; Kovacevic, Ann-Marie; Roberts-Thomson, Philip; Stanton, Tony; Hamilton-Craig, Christian; Wahi, Sudhir; La Gerche, Andre; Hare, James L.; Selvanayagam, Joseph; Maiorana, Andrew; Venn, Alison J.; et al.
Abstract : Background: Exaggerated exercise blood pressure (EEBP) during clinical exercise testing is associated with poor blood pressure (BP) control and cardiovascular disease (CVD). Type-2 diabetes (T2DM) is thought to be associated with increased prevalence of EEBP, but this has never been definitively determined and was the aim of this study. Methods: Clinical exercise test records were analyzed from 13 268 people (aged 53±13 years, 59% male) who completed the Bruce treadmill protocol (stages 1–4, and peak) at 4 Australian public hospitals. Records (including BP) were linked to administrative health datasets (hospital and emergency admissions) to define clinical characteristics and classify T2DM (n=1199) versus no T2DM (n=12 069). EEBP was defined as systolic BP ≥90th percentile at each test stage. Exercise BP was regressed on T2DM history and adjusted for CVD and risk factors. Results: Prevalence of EEBP (age, sex, preexercise BP, hypertension history, CVD history and aerobic capacity adjusted) was 12% to 51% greater in T2DM versus no T2DM (prevalence ratio [95% CI], stage 1, 1.12 [1.02–1.24]; stage 2, 1.51 [1.41–1.61]; stage 3, 1.25 [1.10–1.42]; peak, 1.18 [1.09–1.29]). At stages 1 to 3, 8.6% to 15.8% (4.8%–9.7% T2DM versus 3.5% to 6.1% no-T2DM) of people with 'normal' preexercise BP (<140/90 mm Hg) were identified with EEBP. Exercise systolic BP relative to aerobic capacity (stages 1–4 and peak) was higher in T2DM with adjustment for all CVD risk factors. Conclusions: People with T2DM have higher prevalence of EEBP and exercise systolic BP independent of CVD and many of its known risk factors. Clinicians supervising exercise testing should be alerted to increased likelihood of EEBP and thus poor BP control warranting follow-up care in people with T2DM.